TESTING RESEARCH ON PHASED ARRAY ULTRASONIC OF FILLET WELD OF RAPID-COOLING HEAT EXCHANGER - OU XuSheng; QI LingMin; HAN TaiKun (Jixie qiangdu)
It is important for related equipment in the safe and stable performance that the integrality quality of the fillet welds of rapid-cooling heat exchanger. However,a few defects of the weld can ’t be detected effectively based on the nondestructive testing methods of existing standard. This paper provides a measurable method for testing fillet weld of rapid-cooling heat exchanger which is phased array ultrasonic testing technique. A simulation block is made for validating the phased array ultrasonic testing system,which is according to the size and shape of a fillet weld on headers of rapid-cooling heat exchanger.Firstly,the size and placement of the probe is determined by simulating on software. Finally,the practicability of phased array ultrasonic testing on fillet weld of rapid-cooling heat exchanger is proved by testing artificial defects on simulation block.